Історiя становлення та розвитку дослiджень фiзики Сонця у Львовi: роки, люди, наукові здобутки - Ковальчук, М. (Праці наукового товариства ім. Шевченка, 2011)
The paper presents a short historical description of the the first solar observations in Lviv based on the archive materials. Also the history of establishment and development of solar physics department at Astronomical Observatory at Ivan Franko National University of Lviv is presented. The development of observational studies is described as well as theoretical investigations in solar physics It is emphasized that the achievements in this branch of science is the result of both the initiative and the clear guidance of the whole department sta. The positive influence of scientific ties of Lviv astrophysicists with other leading astronomical institutions is highlighted. The prospects of further development of research trends at the Solar physics department are drafted.